Penerapan Model Dick and Carrey pada Pembelajaran PAI di MA Al-Falah Nagreg - Nugraha, Mulyawan Safwandy; Saputra, Wahyu Andi (Lembaga Yasin AlSys, 2024)
This research uses a qualitative approach by utilizing interviews and observations as the main instruments to collect in-depth data regarding the application of the Dick and Carrey Model in Islamic Religious Education (PAI) learning at MA Al-Falah Nagreg. The research results highlight the dominant learning pattern in schools, which relies more on conventional methods with teacher presentation of material and student involvement through note-taking and limited discussion sessions. Factors that influence the decision not to adopt the Dick and Carrey Model, such as practical obstacles in its implementation, established school policies, financial constraints, and considerations of educational values and philosophy, are highlighted in the eval_uation of school obstacles. Furthermore, this article details alternative learning models that can be implemented to increase the effectiveness of PAI learning at MA Al-Falah, including project-based approaches, cooperative learning, and the flipped classroom concept, with the hope of being able to overcome these obstacles and be in line with the characteristics and values of educational values embraced by the school.